Law on Corporate Governance - The Development Trends of the World and the Problems Posed to Vietnam - Ngoc Hien, Ho; Thai Ha, Nguyen; Dang Hai, Phan; Dinh Lanh, Cao (ExcelingTech, 2020)
Abstract In recent years, following the trend of extensive international integration, prestigious organizations in the world such as OECD, World Bank, IFC,... and countries are trying to develop effective legally regulations and principles on corporate governance. In general, these rules basically affect each other so they have certain similarities which are all emphasizing the importance of independence, transparency and accountability in corporate governance. By researching the development trends of world law on corporate governance, the article will give valuable experiences for perfecting corporate governance laws in Vietnam.